2021
DOI: 10.1039/d1nr01506k
|View full text |Cite
|
Sign up to set email alerts
|

Acidic tumor microenvironment-sensitive liposomes enhance colorectal cancer therapy by acting on both tumor cells and cancer-associated fibroblasts

Abstract: Cancer-associated fibroblasts (CAFs) play a crucial role in facilitating tumor invasion and metastasis, which act as the “soils” in tumor microenvironment (TME). Accordingly, it would be a promising strategy to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…This observation was consistent with the results of prior studies involving B16, CT26, and 4T1 tumors mixed with NIH3T3 fibroblasts. 14 16 Western blotting revealed that FAP was highly expressed in the NIH3T3-FAP cell line, whereas was not expressed in MC38 and CT26 cells (Fig. 1b ).…”
Section: Resultsmentioning
confidence: 99%
“…This observation was consistent with the results of prior studies involving B16, CT26, and 4T1 tumors mixed with NIH3T3 fibroblasts. 14 16 Western blotting revealed that FAP was highly expressed in the NIH3T3-FAP cell line, whereas was not expressed in MC38 and CT26 cells (Fig. 1b ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent research has shown that the normal fibroblasts could be activated by tumor cells. , To mimic the hepatoma TME in vitro, LX-2 cells were incubated with the condition medium of 7402 cells for 24 h. A cellular immunofluorescence assay was performed to explore whether the cocultured model was established successfully. Briefly, LX-2 cells were seeded into cover-glass bottom dishes and treated with the 7402 cell condition medium for 24 h. Then, the solutions were removed, and the cells were treated with various formulations.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous research reported that liposomes were safe carriers for drug delivery due to their biocompatible and lower cytotoxicity. 32 In this study, the in vitro cytotoxicity of various formulations was assessed using the MTT assay. As shown in Figure 4A,B, all the drug formulations showed concentration-dependent cytotoxicity.…”
Section: Combination Therapy Inhibits the Activation Ofmentioning
confidence: 99%
“…In recent years, tumor microenvironment (TME) responsive liposomes have received attention from many researchers [ 77 ]. These liposomes underwent a conformational change when exposed to microenvironmental stimuli (such as pH, reactive oxygen species (ROS), temperature, magnetic field or enzyme) in order to achieve specific release of the CRISPR/Cas9 system and improve gene editing efficiency [ 78 ].…”
Section: Kinds Of Nps-based Crispr/cas9 Systemmentioning
confidence: 99%